Using Factor Analysis to Specify the Most Important Factors which Affect the Academic Achievement at Students of Secondary Level: دراسة تطبيقية بمدارس شركة سكر كنانة المحدودة للعام الدراسي )2019 - 2020م( - د. خالد رحمة الله خضر قناوي,; أ. نعيم محمود سبيل علي, (White Nile Journal for Studies and Research, 2021)
This study aims to apply a global analysis method to identify the most important factors affecting academic achievement among secondary students in Kennan Sugar Company Limited schools. The data was collected through questionnaire that included (47) variables and the consistency was calculated by the Fakenbakh coefficient and the validity of the content and The correlation matrix, the use of the descriptive analytical approach, one of the most important results of the study: 17 workers were extracted which explaining (65.5%) of the total variance, According to degree of it, impact on achievement, based on the study's hypotheses most influencing factors on academic achievement, the most important of which are; the economic factor which explains 28,8% of the total disparity, this percentage indicates that this factor is of a great degree of importance and among its variables is the low economic of the family that pushes students to not be interested in studying, numbers of daily meals for the family and the means of transportation to and from the school. The social factor explains (19,3%) of the total disparity and among its most important variable is the educational level of the father and his job, family quarrels affect the level of achievement, the separation of the father and mother (divorce), the numbers of females in the family and parents duty. The academic factor which explains (12,9%) of the total variance. The most important variables of which students lack of assimilation by some teachers. The student can focus more on the subject when his or her family's income stabilizes.As for The least influencing factors on achievement, the most important of which is the school age that explains (2,14%) of the total variance of its variables. The factor residential environment represented in the variables, uncomfortable housing which negative affect my academic achievement, lighting at home. Academic specialization scientific or literary, father second marriage. Accordingly, the study recommended the: sports, recreational programs and school trips And raising their teaching skills such as inverted education, and create good relation with the school.